Antioxidant enzyme and malondialdehyde values in social phobia before and after citalopram treatment - Atmaca, M; Tezcan, E; Kuloglu, M; Ustundag, B; Tunckol, H (Dr Dietrich Steinkopff Verlag, 2004)
A growing body of evidence indicates that oxidative stress is involved in the etiopathogenesis of some psychiatric disorders. In our previous study, we have found that social phobia (SP) seems to be associated with elevated antioxidant enzymes and malondialdehyde (MDA) levels, a lipid peroxidation product. In the present investigation, we sought to determine whether the increased radical burden observed in patients with SP would be attenuated with alleviation of symptoms. Thirty-nine patients diagnosed with generalized SP and 39 healthy controls participated in this study. The measurements of MDA, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase (CAT) were performed before and after a period of 8 weeks of citalopram treatment. In this period, the patients received citalopram but controls did not. The initial dose of citalopram was 20 mg, with 20 mg increments occurring every 2 weeks, to a maximum dose of 60 mg, with the mean daily dose of 38.9 +/- 13.3 mg/day. All patients were evaluated by using Liebowitz Social Anxiety Scale (LSAS). The mean MDA, SOD, GSH-Px and CAT levels of the patient group at baseline were significantly higher than those of controls. Antioxidant enzymes and MDA levels decreas significantly through citalopram treatment. Significant and positive correlation was observed between decrease in the total LSAS scores, and SOD or CAT levels. In conclusion, our results suggest that, in patients with SP, subchronic treatment with citalopram may decrease antioxidant enzymes and MDA values and that they are state markers of SP because they return to normal values with treatment.
Keywords: antioxidant enzyme; citalopram; malondialdehyde; social phobia